ACL Fibers Near the Lateral Intercondylar Ridge Are the Most Load Bearing During Stability Examinations and Isometric Through Passive Flexion. (October 2016) - Nawabi, Danyal H.; Tucker, Scott; Schafer, Kevin A.; Zuiderbaan, Hendrik Aernout; Nguyen, Joseph T.; Wickiewicz, Thomas L.; Imhauser, Carl W.; Pearle, Andrew D.
Background: The femoral insertion of the anterior cruciate ligament (ACL) has direct and indirect fiber types located within the respective high (anterior) and low (posterior) regions of the femoral footprint. Hypothesis: The fibers in the high region of the ACL footprint carry more force and are more isometric than the fibers in the low region of the ACL footprint. Study Design: Controlled laboratory study. Methods: Ten fresh-frozen cadaveric knees were mounted to a robotic manipulator. A 134-N anterior force at 30° and 90° of flexion and combined valgus (8 N·m) and internal (4 N·m) rotation torques at 15° of flexion were applied simulating tests of anterior and rotatory stability. The ACL was sectioned at the femoral footprint by detaching either the higher band of fibers neighboring the lateral intercondylar ridge in the region of the direct insertion or the posterior, crescent-shaped fibers in the region of the indirect insertion, followed by the remainder of the ACL. The kinematics of the ACL-intact knee was replayed, and the reduction in force due to each sectioned portion of insertion fibers was measured. Isometry was assessed at anteromedial, center, and posterolateral locations within the high and low regions of the femoral footprint. Results: With an anterior tibial force at 30° of flexion, the high fibers carried 83.9% of the total anterior ACL load compared with 16.1% in the low fibers ( P < .001). The high fibers also carried more anterior force than the low fibers at 90° of flexion (95.2% vs 4.8%; P < .001). Under combined torques at 15° of flexion, the high fibers carried 84.2% of the anterior ACL force compared with 15.8% in the low fibers ( P < .001). Virtual ACL fibers placed at the anteromedial portion of the high region of the femoral footprint were the most isometric, with a maximum length change of 3.9 ± 1.5 mm. Conclusion: ACL fibers located high within the femoral footprint bear more force during stability testing and are more isometric during flexion than low fibers. Clinical Relevance: It may be advantageous to create a "higher" femoral tunnel during ACL reconstruction at the lateral intercondylar ridge.